3D printing in the teaching of anatomy of cerebrovascular diseases (Research, Society and Development, 2022)
The production of models from 3D printing is an extremely innovative technique to be used in teaching practices. In addition to replicating the pieces already existing in the anatomy laboratory, it can produce other pieces based on clinical cases recorded from image exams, in a detailed way. Thus, the present study reports the technical applications of three-dimensional printing in teaching the anatomy of cerebrovascular diseases. This is a descriptive study, based on an integrative literature review, using articles that addressed the topic, found by searching for studies with the MeSH terms “three-dimensional printing” and “cerebrovascular diseases”. In universities of health sciences, the use of three-dimensional models has been increasingly common. The construction of 3D parts can be used as a tool for a greater understanding of the patient regarding their condition, to improve preoperative planning and even the teaching of highly complex surgical techniques, such as in therapeutic procedures for arteriovenous malformations and brain aneurysms. In addition to the use of 3D printing in the teaching-learning process of residents and academics, models have become a very effective tool in increasing patients' understanding of cerebrovascular diseases.